A topologically gradient body centered lattice design with enhanced stiffness and energy absorption properties. (15th July 2022) - Zhang, Siyuan; Yang, Fan; Li, Puhao; Bian, Yijie; Zhao, Jinfeng; Fan, Hualin
Highlights: Gradient lattice structures were designed by gradiently varying the BCC cell center vertex. Python script was employed to architect lattice structures with different gradient. Multi-jet Fusion technique was used to fabricate gradient lattice samples with PA 12. Topology gradient can change the deformation mode and improve the mechanical properties. Abstract: Lattice structures have been widely used in biomedicine, transportation, infrastructure, and other engineering fields due to their high specific strength, strong energy absorption capacity, and tunable mechanical property. Existing researches mainly focus on the uniform lattice structure or gradient lattice structure with varying density, with the design potential of lattice structure not fully exploited. In this study, inspired by the functionally graded material, a novel topologically gradient lattice structure with varying cell topology is proposed to realize spacial adjustability of the mechanical properties. The new lattice structure evolves from the classical body-centered cubic (BCC) lattice, with the body center positions varying gradiently from cell to cell along the specified directions. The prototypes of the new lattice are additively manufactured by the Multi-Jet Fusion (MJF) technology and quasi-statically compressed by the universal testing machines. Experimental and numerical simulation results reveal that the proposed structure topology gradient can significantly improve both the stiffness and the energy absorption capacity compared with the classical BCC lattice structures. It is found that the mechanical properties of the topologically gradient lattice structures are sensitive to the gradient direction, the gradient magnitude and the loading direction. This study expands the design space of lattice structures by introducing the topology gradient of the composing cells across the space. In this way, further improvement in the mechanical properties of lightweight lattice structures can be achieved.